2019
DOI: 10.1001/jamaoncol.2019.0127
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Frequently Mutated Genes and the Association With Tumor Mutation Load

Abstract: 2. Mandelker D, Zhang L, Kemel Y, et al. Mutation detection in patients with advanced cancer by universal sequencing of cancer-related genes in tumor and normal dna vs guideline-based germline testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Coincidentally, Muc16, which is frequently mutated and encodes the cancer antigen CA-125, was demonstrated to be associated with a higher TMB and favorable survival outcome of patients with gastric cancer (50). Moreover, Yosef found that in addition to Muc16, most (210 of 212) frequently mutated genes (defined as >1%) in gastric cancer were associated with a significant tumor mutation load (51). The observations in Muc16, which was the second-longest gene in the genome, also support the correlation between higher mutational burden and the mutated status of a gene with a long exon.…”
Section: Discussionmentioning
confidence: 99%
“…Coincidentally, Muc16, which is frequently mutated and encodes the cancer antigen CA-125, was demonstrated to be associated with a higher TMB and favorable survival outcome of patients with gastric cancer (50). Moreover, Yosef found that in addition to Muc16, most (210 of 212) frequently mutated genes (defined as >1%) in gastric cancer were associated with a significant tumor mutation load (51). The observations in Muc16, which was the second-longest gene in the genome, also support the correlation between higher mutational burden and the mutated status of a gene with a long exon.…”
Section: Discussionmentioning
confidence: 99%
“…The undefined driving or accompanying role of DDR mutations in different pathologic types of PLC may also account for the different role of TMB in survival prognosis. More importantly, TMB may be the outcomes, not driving factors, from the oncogenic alterations which lead the poorer survival for some patients (45).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the more frequent MUC16 mutation was associated with a higher TML (Li et al, 2018). Maruvka et al argued that a larger MUC16 mutation frequency could only be an accompanying result of high TML (Maruvka et al, 2019). MUC16 was also present in our 52-gene list.…”
Section: Discussionmentioning
confidence: 74%